Bagus Pemetaan Partisipatif Bidang Tanah Berbasis Data Peta Kerja BPN di Lingkungan Satria, Kelurahan Penarukan - Sukaantara, Gede Gita; Treman, Wayan; Putra, I Wayan Krisna Eka (Universitas Pendidikan Ganesha, 2024)
The Satria neighborhood is an area where the data on the land plot work map is not neat and many land plots have not been plotted. To tidy up and complete the data on land parcels that have not been plotted, a participatory mapping program of land parcels based on work map data from BPN is carried out. This study aims to map land plots in the Satria Environment. The methods used for this study are a combination of qualitative and quantitative methods with a descriptive approach, qualitative methods in field mapping involve in-depth data collection, such as surveys, interviews, and observations, and quantitative methods are used in calculating the area of each land plot data. The results of this study show that in the Satria Environment area there are 3 classifications of land plots, namely, certified land plots with an appropriate area of 421 plots of land with a total area of 14.03 Ha with a percentage of 32.3%, certified land plots with an inappropriate area of 88 plots of land with a total area of 3.00 Ha with a percentage of 6.9% and plots of mapping results totaling 268 plots of land with a total of 268 plots of land with a total of The area reached 26.37 Ha with a percentage of 60.8%.